Investigation on the co-extrudability and spheronization properties of wet masses - Pinto, JF (2015)
In the present work, preliminary results of co-extrusion and spheronization of wet masses are reported. A ram co-extruder, manufactured in-house, was designed with two concentric single dies mounted on two concentric and independent chambers. This equipment has allowed the production of three types of extrudates. (rod or solid extrudates, tubular or hollow extrudates. and co-extrudates). Different wet mixtures of microcrystalline cellulose, lactose, a non-soluble in water dye and water were produced and used to feed the chambers of the ram co-extruder. Extrusions of the wet masses were carried out at different speeds of the ram (25-400 mm/min). The extrudates were evaluated according to surface characteristics (by visual inspection), force of extrusion and duration of steady-state (after recording the force applied to the ram and its displacement). Simultaneously, for each process of extrusion it was possible to assess the angles of convergence to the bottom of the chambers for both the external and internal chambers. These angles reflected the high complexity of the extrusion occurring on the external chamber in consequence of its annular geometry, in which the bisecting-line was not parallel to the axis of the extruder, by opposition to the converging angle in the internal chamber, where the bisecting-line was perfectly aligned to the axis of the extruder. Variations in the amount of water in the formulations and the speed of extrusion affected both the production and the quality of the extrudates and their ability to provide pellets. The rod extrudates were the easiest to produce and the relationships between the formulations, the processing conditions and the properties of the extrudates were immediately apparent. On the other hand, co-extrudates were more complex to characterise, although identical relationships between formulations, processing conditions and the properties of the co-extrudates were observed as for the rod extrudates. Different batches of extrudates (rod, tubular and co-extrudates) were spheronized to a maximum spheronization time of 10 min at 1000 rpm. The pellets were characterized with respect to size, size distribution, sphericity and density. Results have shown that for a larger diameter of the co-extrudates, the pellets produced were bigger (approximate to 3.38 mm) than the pellets produced from rod extrudates (1.22 mm). For longer times of spheronization, the aspect ratio and the density increased for both pellets produced from rod (0.95 and 1.46 g/cm(3)) and co-extrudates (0.90 and 1.47 g/cm(3)). The study has shown the potential of this new technology in providing a product with advantages over the traditional spheres produced by extrusion and spheronization. (C) 2001 Elsevier Science B.V. All rights reserved.